Safety of Supracostal Percutaneous Nephrolithotomy in Paediatric Population: A Single Centre Experience - Muhammad Kamran Khan, Naqib Ullah, Nazim Mohayuddin, Naveed Haroon, Ahmad Nawaz, Muhammad Kamran Khan, Naqib Ullah, Nazim Mohayuddin, Naveed Haroon, Ahmad Nawaz (Journal of Rawalpindi Medical College, 2022)
Objective The objective of this study is assessment of safety and efficacy of supracostal mini percutaneous nephrolithotomy in pediatric patients. Methodology This is prospective study of patients whose kidney stones were treated with mini percutaneous nephrolithotomy through supracostal approach between February 2019 and Dec 2020.These patients were selected for supracostal puncture based on preoperative ultrasound and CT KUB findings and peroperative assessment of stone burden, stone location and anatomy of pelvicalyceal system. Results Of 80 patients 72(90%) were treated with only one supracostal puncture while additional 2nd puncture was used for 8(10%) patients. Overall stone clearance is 85% only with percutaneous nephrolithotomy and the stone clearance has reached to 95% with ancillary procedures.13% of patient had hydrothorax , 3.75% had urosepsis, 2.75% had bleeding and 1.25 % had perinephric fluid collection. Conclusion This study concludes that the safety and efficacy of supracostal percutaneous nephrolithotomy is same as subcostal pcnl if surgical boundaries are not violated.